PENDEKATAN TOKOH MUSLIM LIBERAL DALAM PENETAPAN NILAI DAN HUKUM ISLAM - Asep Zaenal Ausop (Jurnal Sosioteknologi, 2011)
There are two types of Muslim thinkers / leaders, namely the traditional Muslim thinkers and rational Muslim thinker. Traditional Muslim thinkers are thinkers who are bound by Ahad Hadith and opinions of previous scholars (salafi). Ulema scholars who place the rational mind is in a very high so that ruled out on Sunday and the hadith are not bound by the opinions of ulama salaf. All religious dogma and what rules would be rejected if it does not make sense. In a set of values and Islamic law, they use three methods of approach, namely metaphorical interpretation, interpretation hermeneutics and social historical methods. In the field, often a very sharp clash of ideas between traditional Muslim thinkers with rational Muslim thinker often happens. In the next development, rational figure is increasingly free to use their minds and seemed to underestimate the words of the Apostle and the text of the Koran so that they are called liberal Muslim leaders. Keywords: Metaphoric interpretation, Hermeneutic interpretation, Social history